KOMUNIKASI ANTARPRIBADI GURU DAN MURID PENDERITA KANKER DI “SEKOLAH-KU” PADA YAYASAN KASIH ANAK KANKER INDONESIA- RIAU - Habilla Juli Daska; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Children with cancer have the same rights and opportunities to get education as healthy children in general. “My School” at the Indonesian Cancer Child Love Foundation (YKAKI) – Riau is a school facility that is intended for children with cancer so that they can continue to receive education and do not drop out of school even during treatment and treatment. Interpersonal communication is needed in the learning process between teachers and students with cancer. This research was conducted to determine how openness, empathy, positive attitudes, supportiveness and equality are carried out by teachers and students with cancer at “My School” at the Indonesian Canmcer Child Love Foundation (YKAKI) – Riau. This research uses qualitative research methods with a symbolic interaction approach and is descriptive in nature. The informant in study were teacher, students with cancer and parents of students with cancer using a purposive method. Data collection techniques used are observation, interviews and documentation. The data analysis technique in this study used an interactive model by Miles and Huberman. The technique of checking the validity of the data in this study used participation extension and triangulation. The results showed that the interpersonal communication carried out by the teachers and students with cancer in the learning process went well. The attitude of openness is carried out by asking how the student is, what the student feels, what the student thinks, what the student with cancer wants to learn. The attitude of empathy that is carried out is in the form of verbal and nonverbal. The positive behavior is being friendly and not angry with students with cancer. The supportive attitude is done by giving encouragement, motivation and praise to students with cancer. The equality between teachers and students is by not being patronizing and valuing each other. Interpersonal communication between teachers and students has a positive impact on students with cancer in getting education and fighting the disease. Keyword : Interpersonal communication, teachers, children with cancer